Prostate cancer. Issue 10305 (18th September 2021) - Sandhu, Shahneen; Moore, Caroline M; Chiong, Edmund; Beltran, Himisha; Bristow, Robert G; Williams, Scott G
Summary: The management of prostate cancer continues to evolve rapidly, with substantial advances being made in understanding the genomic landscape and biology underpinning both primary and metastatic prostate cancer. Similarly, the emergence of more sensitive imaging methods has improved diagnostic and staging accuracy and refined surveillance strategies. These advances have introduced personalised therapeutics to clinical practice, with treatments targeting genomic alterations in DNA repair pathways now clinically validated. An important shift in the therapeutic framework for metastatic disease has taken place, with metastatic-directed therapies being evaluated for oligometastatic disease, aggressive management of the primary lesion shown to benefit patients with low-volume metastatic disease, and with several novel androgen pathway inhibitors significantly improving survival when used as a first-line therapy for metastatic disease. Research into the molecular characterisation of localised, recurrent, and progressive disease will undoubtedly have an impact on clinical management. Similarly, emerging research into novel therapeutics, such as targeted radioisotopes and immunotherapy, holds much promise for improving the lives of patients with prostate cancer.